2018
DOI: 10.1088/1361-6528/aad5f5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ni–Pt/Fe–TiO2 nanotube films for photoelectrochemical cathodic protection of 403 stainless steel

Abstract: Iron-doped TiO nanotubes (Fe-TNTs) were prepared by a one step anodization method. Nickel-platinum was then deposited on the surface of these Fe-TNTs samples by an electroless process during different time periods. SEM, XRD and UV-vis absorption spectroscopy was used to study the surface morphologies, composition and optical properties of the synthetic samples. In addition, the impact of coupling the samples prepared with 403 stainless steel on the corrosion of metal under illumination was studied. The corrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The rapid increase and decrease in photocurrent in Fig. 7b show that the charge transport occurs in the film very quickly [18,19,27].…”
Section: Electrochemical Measurementsmentioning
confidence: 86%
See 1 more Smart Citation
“…The rapid increase and decrease in photocurrent in Fig. 7b show that the charge transport occurs in the film very quickly [18,19,27].…”
Section: Electrochemical Measurementsmentioning
confidence: 86%
“…Also our previous studies showed that deposition of nickel-platinum on the surface of Fe-doped TiO 2 nanotube films is a promising technology to improve the PEC cathodic protection to some metals such as 304SS. Usually, the doped ions create additional energy levels into the band structure, which can be used to trap electrons or holes to separate carriers from the bands, thus allowing more carriers to successfully diffuse to the surface [16][17][18][19]. Yu [24].…”
Section: Introductionmentioning
confidence: 99%
“…Research on Fe doping has been carried out as well; iron can enter the lattice of TiO 2 , thus destroying the integrity of TiO 2 and generating defect dots, which plays an important role in provoking the separation of photoelectrons and holes in promoting photocatalytic activity (Li et al, 2007). It has been found that iron ions can improve the photocatalytic activity of TiO 2 , and TiO 2 doped with iron can be used as an energy storage agent, which can maintain corrosion resistance for a long time in the dark (Liu et al, 2014;Momeni et al, 2018).…”
Section: Metal-doped Tio 2 Materialsmentioning
confidence: 99%
“…Titanium dioxide (TiO2) has attracted extensive attention as an efficient PCP material due to its low cost and good photosensitivity [15][16][17]. Among its numerous existing structures, one-dimensional (1D) TiO2 nanorods (TNRs) exhibit good PCP performance associated with its symmetrical 1D structural design that can suppress the e -/h + pairs recombination effectively [18].…”
Section: Introductionmentioning
confidence: 99%